Silver Nanoparticles Biosynthesis Using Mangosteen (Garcinia Mangostana L.) Rind Extract For Environmentally Friendly Liquid Disinfectant Active Ingredients - Abdul Haris Haris Watoni; La Ode Ahmad Nur Ramadhan; Muhammad Daffa Rahmatullah; Angelina Ike Dwiyanti Kalpen Bunga; Supardi Supardi (Chemistry Department, The University of Brawijaya, 2022)
Disinfectant is one of the materials that can be used to inhibit the growth of pathogenic microorganisms, but most of the disinfectants used in the community are disinfectants made from synthetic chemicals that are harmful to the environment. The purpose of this study was to synthesize and evaluate the antimicrobial activity of silver (Ag) nanoparticles- mangosteen rind extract as an active ingredient in an environmentally friendly disinfectant formula. The synthesis process of silver nanoparticles was carried out by adding a bioreductant of mangosteen rind extract into a 0.01 M AgNO3 solution precursor with a variation of the precursor:bioreductor volume ratio of 1:1, 1:2, 1:3, 1:4, 1:5, and 1: 6. The results of the analysis with UV-Vis spectroscopy showed that the silver nanoparticles of mangosteen rind extract had good stability. The decrease in the absorption peak in the FTIR spectrum at a wave number of 3390.86 cm-1 indicates the contribution of the –OH group in the bioreductant compound in the reduction process of silver nanoparticles. PSA analysis and digital microscopy showed that the diameter of the synthesized silver nanoparticles with a volume ratio of bioreductor: precursor 1:1 and 1:2 were 82.33 nm and 356.2 nm, respectively. The antimicrobial activity test showed that the active ingredient mixture of silver-mangosteen rind extract with a composition of 1:1 had the best activity in inhibiting the growth of gram-positive Staphylococcus aureus and gram-negative Eschericia coli bacteria. The results of this study indicate that silver nanoparticles extracted from mangosteen rind are good active ingredients for environmentally friendly liquid disinfectants.